The Effect of Enterprise Risk Management (ERM) on Company Value in Mining Companies Listed on The Indonesia Stock Exchange - Yoga Purwita Kurniawan; Isnurhadi; Marlina Widiyanti; Mohamad Adam (CV. Syntax Corporation Indonesia, 2024)
The purpose of this study is to obtain empirical evidence of the influence Enterprise Risk Management, Size, Return on Asset, Managerial's Ownership on the Value of Mining Companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 20 companies with a research period from 2019-2021 so that there were 60 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that ROA has a significant positive effect, ERM,Size, and Managerial's Ownership has no effect on firm value. The implication of this research is that companies must pay attention to profitability and those that can affect stock prices so that company value can increase.